The association between adverse childhood experiences and traumatic brain injury/concussion in adulthood: A scoping review protocol. Issue 10 (11th October 2017) - Ma, Zechen; Bayley, Mark T; Perrier, Laure; Dhir, Priya; Dépatie, Lana; Comper, Paul; Ruttan, Lesley; Munce, Sarah EP
Abstract : Introduction: Exposure to adverse childhood experiences (ACEs) is a significant risk factor for physical and mental illnesses later in life. Concussion or traumatic brain injury is a challenging condition where preinjury factors may interact to affect recovery. The association between ACEs and traumatic brain injury/concussion is not well mapped in any previous reviews of the literature. Using a scoping review methodology, the research question that will be addressed is: what is known from the existing literature about the association between ACEs and traumatic brain injury/concussion in adults? Methods and analysis: The methodological frameworks outlined by Arksey and O'Malley and Levac et al will be used. All original studies in English published since 2007 investigating ACEs and traumatic brain injury/concussion outcomes will be included with no limitations on study type. Literature search strategies will be developed using medical subject headings and text words related to ACEs and traumatic brain injury/concussions. Multiple electronic databases will be searched. Two independent reviewers will screen titles and abstracts for full-text review and full texts for final inclusion. Two independent reviewers will extract data on study characteristics for ACE exposure and traumatic brain injury/concussion outcomes. Extracted data will be summarised quantitatively using numerical counts and qualitatively using thematic analysis. Dissemination: This review will identify knowledge gaps on the associations between ACEs and traumatic brain injury/concussion and promote further research. Knowledge translation will occur throughout the review process with dissemination of project findings to stakeholders at the local, national and international levels.